AB0471 VITAMIN D SUPPLEMENTATION IN SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS WITH VITAMIN D DEFICIENCY AND INSUFFICIENCY: THE EFFECT ON DISEASE ACTIVITY, FATIGUE AND INTERFERON SIGNATURE GENE EXPRESSION. (June 2019) - Magro, Rosalie; Saliba, Christian; Camilleri, Liberato; Scerri, Christian; Borg, Andrew
Abstract : Background: Vitamin D deficiency is highly prevalent among patients with systemic lupus erythematosus (SLE) [1]. Evidence from multiple studies has shown that vitamin D deficiency in SLE is associated with a higher disease activity [2]. There is conflicting evidence with regards to the relationship between fatigue and vitamin D level [3, 4]. Objectives: The principal aim of this study was to establish any potential effect on the level of fatigue, disease activity (measured by SLE disease activity index-2K (SLEDAI-2K)) and interferon signature gene expression, from vitamin D supplementation to SLE patients with vitamin D deficiency or insufficiency. Methods: 33 SLE patients, 13 with vitamin D deficiency and 20 with vitamin D insufficiency, gave informed consent to participate in this 12 month prospective study. Their participation consisted of an interview, filling of the Fatigue Severity Scale (FSS), and blood tests. The patients were advised to take vitamin D3 8000IU daily for 8 weeks if they were vitamin D deficient, or 8000IU daily for 4 weeks if they were insufficient. This was followed by 2000IU daily maintenance. The patients were re-assessed after 6 and 12 months of vitamin D supplementation. RNA was extracted from whole blood taken from the patients at baseline and after 6 months of vitamin D supplementation. The expression of 12 interferon signature genes was measured in the extracted RNA by using QuantiGene Plex technology. Approval to carry out this study was obtained from the University Research Ethics Committee. Results: 87.9% of SLE patients studied were female. The mean age was 47.6 years and the mean duration of SLE was 13.8 years. Table 1 shows the results obtained for several variables at baseline, after 6 months and after 12 months. The expression of all 12 interferon signature genes measured, was noted to decrease following 6 months of vitamin D supplementation. This reached statistical significance for two of the genes measured (OAS1, p=0.014; SOCS1, p=0.003). Conclusion: The results indicate that vitamin D supplementation in SLE patients who are deficient or insufficient, results in an improvement in disease activity, and possibly also in the level of fatigue. This could be explained by the decrease in the expression of interferon signature genes. References: [1] Kamen DL, Aranow C. The link between vitamin D deficiency and systemic lupus erythematosus. Curr Rheumatol Rep 2008; 10: 273–280. [2] Sahebari M, Nabavi N, Salehi M. Correlation between serum 25(OH)D values and lupus disease activity: an original article and a systematic review with meta-analysis focusing on serum VitD confounders. Lupus 2014; 23:1164-77. [3] Ruiz-Irastorza G, Egurbide MV, Olivares N, Martinez-Berriotxoa A, Aguirre C. Vitamin D deficiency in systemic lupus erythematosus: prevalence, predictors and clinical consequences. Rheumatology 2008; 47:920–923. [4] Ruiz-Irastorza G, Gordo S, Olivares N, Egurbide MV, Aguirre C. Changes in vitamin D levels in patients with systemic lupus erythematosus: Effects on fatigue, disease activity, and damage. Arthritis Care Res 2010; 62:1160–1165. Disclosure of Interests: None declared